Ship construction - Eyres, David J; Bruce, George J. (Butterworth-Heinemann, 2012)
"Acting as both a professional reference on current approaches in shipyard practice and a comprehensive introduction for students in any marine discipline, Ship Construction covers the complete construction process, from ship specification to completed vessel." -- Page 4 of cover.